Pengaruh Pembelajaran Kolaboratif Terhadap Keterampilan Pemecaahan Masalah Siswa SMK Negeri 1 Kendit - Yudis Setiawan; Ary Wijaya; Miftahus Surur; Dassucik Dassucik (CV. Aksara Global, 2024)
This research aims to explore and analyze the influence of collaborative learning on students' problem solving skills at SMK Negeri 1 Kendit. The literature review method was used as the main research approach to develop a conceptual framework and gain an in-depth understanding of this topic. Collaborative learning is identified as a learning model that encourages active interaction between students, promotes joint problem solving, and improves social skills. A literature review involves searching related sources in the fields of education, collaborative learning, and students' problem-solving skills. The results of the literature analysis show that collaborative learning can make a positive contribution to the development of students' problem solving skills in vocational schools. Interaction between students, self-empowerment, and joint problem solving through collaborative learning can help students develop skills such as communication, teamwork, and problem solving which are key to success in the work environment. This research provides an important contribution in the context of curriculum development and learning strategies at SMK Negeri 1 Kendit, by identifying collaborative learning principles that can be applied to improve students' problem solving skills. The practical implications of this research involve the formulation of recommendations for teachers and policy makers in the field of education to increase the effectiveness of collaborative learning in the context of vocational high schools.